Assessing amino acid utilization in young Nellore steers fed high-concentrate diets with different sources and levels of nitrogen - Souza, Vinícius Carneiro de [UNESP]; Messana, Juliana Duarte [UNESP]; Batista, Erick Darlisson; Gomes Carvalho Alves, Kênia Larissa [UNESP]; Lino Dias, Ana Verônica [UNESP]; Marra Campos, Letícia; de Oliveira Lima, Laís [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Rodrigues Faria, Letícia; Macêdo Carvalho, Geovany [UNESP]; Pires, Alexandre Vaz; Berchielli, Telma Teresinha [UNESP] (My University, 2020)
The aim of this study was to evaluate the availability and utilization of individual amino acids (AA) in young Nellore steers fed high-concentrate diets with different levels and sources of nitrogen (N). Six castrated Nellore steers, cannulated in the rumen, duodenum and ileum were randomly assigned in a 6 × 6 Latin square design arranged in a 2 × 3 factorial, which consisted of 3 protein sources (soybean meal plus urea (SU), corn gluten meal (CGM) and dry distillers grains (DDG)) and 2 dietary crude protein (CP) levels (110 and 140 g/kg dry matter). Arginine concentration in rumen microbial crude protein (MICP) was greater in steers fed diets containing DDG (P = 0.014). Histidine concentration in MICP was greater (P = 0.015) in steers fed CGM or DDG diets. Lysine concentration in MICP was greater (P = 0.050) as the protein level (PL) increased in the CGM diets. Steers fed diets containing DDG had greater NEAA flow (P = 0.049) and tended (P ≤ 0.08) to have greater non-essential AA (NEAA), arginine, leucine, lysine, proline and serine flow from MICP compared to those fed SU diets. Histidine and glutamate from MICP had a greater supply (P = 0.01) by the dietary inclusion of CGM or DDG. Steers fed CGM or DDG tended (P ≤ 0.07) to have greater EAA, arginine, isoleucine and valine supply from rumen undegraded protein (RUP). The Leucine supply from RUP was greater (P = 0.03) in the sources CGM or DDG. Increasing the protein level (PL) from 110 to 140 g/kg CP in SU diets reduced (P ≤ 0.04) the digestibility of isoleucine, leucine, and tyrosine. In contrast, the digestibility of leucine, methionine, aspartic acid, glutamate, glycine, serine, and tyrosine was improved (P ≤ 0.05) by the increase in the PL in DDG diets. Plasma leucine and phenylalanine concentration was greater (P ≤ 0.047) in steers fed diets containing CGM or DDG. Plasma leucine and valine concentration was greater (P ≤ 0.042) in steers fed diets containing 140 g/kg of CP. Arginine and histidine utilization were greater (P ≤ 0.013) in steers fed diets containing 110 g/kg CP with DDG and 140 g/kg CP with CGM. Steers fed the diet containing 110 g/kg CP and DDG showed greater (P ≤ 0.04) isoleucine, lysine, phenylalanine, threonine, valine, alanine, aspartic, glutamate, serine, and tyrosine use efficiency than those fed other diets, except for those fed the diet containing 140 g/kg CP with CGM which did not differ. The AA use efficiency is affected by dietary protein levels and sources. Our results suggest that it is possible to increase the supply of essential AA by the use of CGM or DDG (RUP sources).
Keywords: Amino acids; Bos indicus; Efficiency; Feedlot diets